Діагностика психологічної готовності до виходу на пенсію осіб пізньої зрілості - Магдисюк, Людмила Іванівна; Mahdysiuk, Liudmyla I. (Південноукраїнський національний педагогічний університет імені К. Д. Ушинського, 2016)
У статті розкривається процедура та методика проведення напівструктурованого інтерв’ю при дослідженні психологічної готовності осіб пізньої зрілості до виходу на пенсію. Представлено правила складання запитань при розробці напівструктурованого інтерв’ю, приклади основних запитань при роботі з особами пізньої зрілості. Описано основні етапи, завдання та вимоги що до проведення та організації напівструктурованого інтерв’ю у фокус-групах.

Retirement affects physical and psychic health of a person, who is going through the great changes of social status, feel-ing professional isolation, which causes the necessity of adjusting to the new life conditions. Human life is considered to be the adjustment to the environment from the very beginning and to the very end. Psychological adjustment is effected by the means of adaptation of a person to the present social demands in the process of matching individual values and social stan-dards. The review of domestic studies of the phenomenon of psychological readiness of a person for the retirement highlights the lack of favourable and valid methodological instruments. It stands to mention that psychological readiness for the retire-ment is characterized by the high level of the strength of inhibitory processes, motility of the nervous processes, adaptability, sociability, conservatism and anxiety. Considering the tasks of studying the issue of psychological readiness of a person for the retirement and the results of the theoretical and empirical researches, the method of semi-structured interview for a psy-cholinguistic study of the problem has been chosen. The semi-structured interview has some advantages, and compared with a questionnaire, it increases the measuring accuracy because face-to-face communication of a psychologist and surveyed during the interview makes conditions for starting mutual confidence, safety and emotional acceptance. The purpose of the semi-structural interview is to afford ground for speaking about one’s life and family without restraint, especially about parents, education, family life, work, as well as express one’s opinion about one’s experience of reaching the retirement age, and de-termine what bothers one during this period of time. In the course of interviewing the respondents have been asked to tell about their professional experience which includes education, career, advanced professional training, and the way their life has changed with the approaching to the retirement age, and whether their life has changed on the whole. To achieve the objec-tives, there have been chosen the method of focus-groups, which can be laconically described as group semi-structured inter-view having a format of group discussion sessions during which the participants are focused on the issues on the researchers’ interest to acquire subjective information from the surveyed. The performance method is organized according to the stated procedure of focus-questioning.
Examination of psychological readiness for retirement of middle aged people
Keywords: напівструктуроване інтерв’ю; психологічна готовність; групове інтерв’ю; зрілість; фокус-група; діагностика; semi-structured interview; psychological readiness; group interview; middle age; focus-group; examination